Exploring the health impacts and inequalities of the new way of working: findings from a cross-sectional study. - Griffiths, Melda Lois; Gray, Benjamin J; Kyle, Richard G; Davies, Alisha R (International Journal of Population Data Science, 2022)
Background Employment is a wider determinant of health, and one of the most striking societal transformations witnessed during the SARS-CoV-2 (COVID-19) pandemic was the sudden shift to working from home (WFH). Within the COVID-19 recovery and efforts to tackle climate change, having large proportions of the workforce WFH has clear benefits. However, the wider adoption of such measures should account for inequalities in accessing home working, the workforce’s preferences for the future, and crucially, the impact that WFH might have on the workforce’s health. Methods A nationally-representative household survey was undertaken across Wales (Public Health Wales’ COVID-19, Employment and Health in Wales study), with cross-sectional data on home-working being collected between November 2020 and January 2021 from 615 employed working-aged adults in Wales (63.7% female, 32.7% aged 50-59). Respondents were asked about their ability to WFH, their perceptions of its impact on their health and their preferences for time spent home-working in future. Findings Over 50% were able to WFH, and showed a preference towards home-working to some capacity, with over a third wishing to WFH at least half the time. However, those living in the most deprived areas, in atypical employment, with high wage precarity or with limiting pre-existing conditions were less likely to report being able to WFH. Of those that could WFH, over 40% reported that it worsened their mental well-being and loneliness, and for people in poorer health, home-working negatively impacted their diet, physical activity, smoking and alcohol use. People aged 30 to 39 and those who lived alone were more likely to report wanting to spend some time working in an office/base instead of at home. Conclusions The new way of working introduces new challenges to preserving workforce mental well-being, regulating health behaviours and tackling inequalities. Our findings shine a light on the negative health impacts associated with WFH (particularly for those already in poorer health), highlight how disadvantaged population sub-groups face further inequalities through being less able to WFH, and provide novel observations of the preferred working models of different sub-groups within the population. Hybrid approaches, combining home and work-based employment are preferred and could alleviate the negative health impacts associated with WFH. Addressing inequalities across the workforce to ensure that everyone is as able to participate in this transformative shift in ways of working is key.